Biosorption of heavy metals by microorganisms: Evaluation of different underlying mechanisms. (November 2022) - Priya, A.K.; Gnanasekaran, Lalitha; Dutta, Kingshuk; Rajendran, Saravanan; Balakrishnan, Deepanraj; Soto-Moscoso, Matias
Abstract: Globally, ecotoxicologists, environmental biologists, biochemists, pathologists, and other experts are concerned about environmental contamination. Numerous pollutants, such as harmful heavy metals and emerging hazardous chemicals, are pervasive sources of water pollution. Water pollution and sustainable development have several eradication strategies proposed and used. Biosorption is a low-cost, easy-to-use, profitable, and efficient method of removing pollutants from water resources. Microorganisms are effective biosorbents, and their biosorption efficacy varies based on several aspects, such as ambient factors, sorbing materials, and metals to be removed. Microbial culture survival is also important. Biofilm agglomerates play an important function in metal uptake by extracellular polymeric molecules from water resources. This study investigates the occurrence of heavy metals, their removal by biosorption techniques, and the influence of variables such as those indicated above on biosorption performance. Ion exchange, complexation, precipitation, and physical adsorption are all components of biosorption. Between 20 and 35 °C is the optimal temperature range for biosorption efficiency from water resources. Utilizing living microorganisms that interact with the active functional groups found in the water contaminants might increase biosorption efficiency. This article discusses the negative impacts of microorganisms on living things and provides an outline of how they affect the elimination of heavy metals. Graphical abstract: Image 1 Highlights: The biosorption capacity of live biomass was higher than that of nonliving biomass. Biomass and metabolization are essential components of heavy metal biosorption. Living biomass exhibited a stronger capacity for biosorption than nonliving biomass. Examined are the obstacles to commercialization that are still there. Microorganisms can use decomposing biomass to produce clean energy.